The Role of The Village Head in Development Planning in Dagouto Kampung, East Paniai District, Paniai Regency - Petrus Yeimo (Budapest International Research and Critics University, 2022)
In Development Planning in Dagouto Village, Paniai Timur District, Paniai Regency